Effects of upstream nozzle geometry on rectangular free jets - Tipnis, T. J. (Depatment of Engineering Systems and Mangement, 2010)
This study is aimed at understanding the effects of changing the upstream nozzle geometry on the development of rectangular free jets. An existing converging rectangular nozzle with an exit aspect ratio of 4 and a circular inlet (AR4 nozzle) has been used as the basic configuration for this work. The study is primarily based on the results of numerical simulations wherein the internal geometry variation is accomplished by changing the inlet aspect ratio (AR,) and the length of the converging section, expressed as a ratio with respect to the length of the nozzle (called 'converging section ratio*, CSR); all the other parameters are kept constant. The results from LDA experiments done on the AR4 nozzle are presented and used as validation data for the CPD simulations. Analyses of the numerical results help in understanding the variation of the jet spreading for different combinations of AR, and CSR. Two parameters are identified for describing the jet development: the cross-over point (XC), defined as the location downstream of the exit where the jet half-velocity-widths (B) along the major and minor axes are equal, and the difference in the half-velocity-widths at 30 nozzle equivalent diameters (Dm) from the exit (AB30), to ascertain the occurrence of axis-switching. For a given AR,, XC varies linearly with CSR; the variation of XC is non-linear with AR, for a constant CSR. The A1330 variation is non-linear with both AR, and CSR; the other variable being kept constant. The data obtained from the simulations are further used to propose two parametric models which can be used to predict the occurrence of axis-switching, within the scope of this work. The parametric models are validated and future work is proposed.
Keywords: Jet Engines